2020
DOI: 10.1111/jopr.13221
|View full text |Cite
|
Sign up to set email alerts
|

Digital Workflow to Merge an Intraoral Scan and CBCT of Edentulous Maxilla: A Technical Report

Abstract: Rehabilitation of edentulous maxilla is a challenging procedure. This technical report describes a new method to superimpose intraoral optical scanning of edentulous maxilla and the CBCT scan using a modified radiographic template. Digital data obtained can be exported and merged into 3D computer guided surgery software. The described technique can increase the predictability and the precision of complete-arch rehabilitation planned by means of computer-assisted implant surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Trueness means the deviation from the true dimensions of the object, while precision describes how much different scans of the same object differ from each other [ 6 , 7 ]. Currently, IOS is potentially considered an alternative to the conventional implant impression to improve patient comfort and speed up workflow [ 8 , 9 ], advantageous features that are also applicable in the field of orthodontics and traditional prosthesis [ 10 , 11 ]. Furthermore, it was demonstrated that digital impressions are sufficiently accurate in tiny spaces; however, in more wide spaces such as those typically associated with edentulous patients, the results are less impressive in terms of both accuracy and speed [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trueness means the deviation from the true dimensions of the object, while precision describes how much different scans of the same object differ from each other [ 6 , 7 ]. Currently, IOS is potentially considered an alternative to the conventional implant impression to improve patient comfort and speed up workflow [ 8 , 9 ], advantageous features that are also applicable in the field of orthodontics and traditional prosthesis [ 10 , 11 ]. Furthermore, it was demonstrated that digital impressions are sufficiently accurate in tiny spaces; however, in more wide spaces such as those typically associated with edentulous patients, the results are less impressive in terms of both accuracy and speed [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prosthetically driven dental implant placement in complete-arch restorations positively contributed to achieve both functionally and aesthetic results [1,2]. Continuous development of digital technologies led to a more comprehensive pre-surgical evaluation of the implant recipient site, avoiding bad results during follow-up period [3,4]. The introduction of the cone-beam computed tomography (CBCT) scan, the ongoing development of intraoral optical scanners (IOS) and modeling softwires allowed the clinician to digitally navigate through the three-dimensional (3D) bone and soft tissue architecture of the virtual patients into implant-planning software [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The development of intraoral scanners (IOSs) has facilitated many dental applications by digitizing tasks previously performed manually through a complex process. [1][2][3] Continuous improvements in their accuracy and scanning speeds have made IOSs more popular. [4][5][6] The accuracy of IOSs has been determined, 4,7-21 and 3dimensional (3D) analysis has been applied to increase the accuracy of IOSs.…”
mentioning
confidence: 99%